The failure of implementation broadcasting regulations in Indonesia-Malaysia border region: case study on free-to-air television in Meranti Regency, Riau Province - Indonesia - Setiawan, Harry; Siti Karlinah,; Hidayat, Dadang Rahmat; Darwis, Yuliandre (Penerbit Universiti Kebangsaan Malaysia, 2021)
Border residents in Meranti Regency still love Malaysian free to air television broadcasts. The broadcasting regulation stipulates that broadcasters must provide free to air access to foster a love of Indonesian television broadcasts and a spirit of nationalism for all levels of society. However, the reality in the field is inversely proportional. An important point that questioned in this research is how the implementation of broadcasting regulations governing equality of access to information and containers of cultural expression in free to air broadcasts for all Indonesian people, especially in border areas. This study aims to reveal the extent of the application of broadcasting regulations in the border region in the context of free to air broadcasts and cultural expression containers in free to air broadcasts. Social action media studies used as an analytical tool to reveal that access and broadcasting infrastructure are a necessity for reaching viewers. The program of the choice model is another analytical tool in uncovering the motives for selecting free to air broadcasts that are loved by border society. The case study method used to find data from the field of a single case that is the implementation of free to air broadcasting regulations in the Indonesian border region of Malaysia. As a result, broadcasting regulations are considered unsuccessful in the context of free to air in the border regions, and the expression of Malay culture has no place on Indonesian television, which in turn, the Malay cultural preference filled with free to air Malaysian broadcasts.